Intergeneric hybridisation between Berula erecta and Helosciadium nodiflorum (Apiaceae). Issue 4 (1st August 2015) - Desjardins, Stuart D.; Leslie, Alan C.; Stace, Clive A.; Schwarzacher, Trude; Bailey, John P.
Abstract: A hybrid between Berula erecta and Helosciadium nodiflorum is reported from Chippenham Fen National Nature Reserve, Cambridgeshire, England. Parentage was investigated using chromosome counts, a maternally inherited chloroplast marker ( rps16‐trnK ), a biparentally inherited nuclear marker (ITS), and fluorescent in situ hybridisation (FISH) using labelled total genomic probes. Two parental genomes were identified in the putative hybrid (2 n = 20), a maternal genome consisting of 9 chromosomes from B. erecta (2 n = 18) and a paternal genome consisting of 11 chromosomes from H. nodiflorum (2 n = 22). The implication of this hybrid for the taxonomy of the group is discussed, and a new hybrid genus is described: × Beruladium (= Berula × Helosciadium ). In overall appearance the hybrid resembles a small, creeping H. nodiflorum, and can be identified in the wild by a combination of characters: (1) the absence of a ring‐mark on the petiole below the lowest pair of leaflets that is characteristic of pure Berula, (2) lower leaves with up to five pairs of leaflets, (3) peduncles varying from shorter than to longer than rays, (4) umbels with several usually untoothed bracts, (5) a relatively long stigma and style, and (6) the absence of ripe fruits. The detection of this taxon is of considerable interest and, as far as we know, it is the first confirmed intergeneric hybrid in the Apiaceae within Europe.